THE EFFECT OF ENTREPRENEURIAL ORIENTATION ON SMALL AND MEDIUM BUSINESS PERFORMANCE IN MEDAN CITY - Dewi SUMA; Budi Alamsyah Siregar BUDI (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Innovation, being proactive, and risk-taking are dimensions of entrepreneurial orientation. The useful application of entrepreneurial orientation aims to improve business performance. This is due to the increasing level of business competition, which requires owners to implement strategies that encourage business excellence. This study aims to examine the impact of innovation, be proactive, and take risks on small and medium enterprises' performance. The research sample, 55 small and medium entrepreneurs who eat fried rice and Padang satay in Medan City. Data analysis, using SPSS 22.00 to test factor analysis (EFA) between variables. A regression test was carried out in the analysis of the proposed hypothesis. The results showed that the innovation variable had a positive and significant effect on performance with a value of β. 640 and significant .000 ≤ 0.05. The proactive variable has a positive and significant effect on performance with a value of β .483 and a significant .003 ≤ .05. However, hypothesis testing results show that the variable taking risks has no effect on performance with a value of β -.249 and is significant .200 > .05.